(23)Na MRI reveals persistent sodium accumulation in tumefactive MS lesions - Huhn, Konstantin; Mennecke, Angelika; Linz, Peter; Tschunko, Franz; Kästle, Nicola; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Linker, Ralf; Engelhorn, Tobias (Journal of the Neurological Sciences, 2017)
Chronic inflammatory demyelinating diseases of the CNS typically show a limited lesion size. However, extended lesions may appear with an atypical configuration. Large lesions with a diameter>2cm accompanied by tumor-like edema are entitled "tumefactive" and may occur in multiple sclerosis (MS) and other demyelinating diseases. Historically, differential diagnosis often requires histological analysis. Therefore, advanced imaging techniques are warranted to allow for a precise non-invasive diagnosis. Cerebral sodium ((23)Na) MRI was recently described as a new method to investigate in vivo sodium accumulation. Indicating extended sodium levels in MS lesions, (23)Na MRI is a promising differential diagnostic tool further elucidating the role of sodium in demyelinating lesions.Repetitive (23)Na MRI measurements in a MS patient with a tumefactive demyelinating lesion providing insight into the medium-term course of cerebral sodium levels.(23)Na MRI depicts persistent lesional sodium accumulation after anti-inflammatory treatment and provides the opportunity of a non-invasive, in vivo analysis of sodium levels in inflammatory CNS lesions without need for contrast enhancing media. As a result of the extended dimension, tumefactive lesions may have an appropriate size for the analysis of inflammatory demyelination by (23)Na MRI with sufficient resolution.
EVALuna2:14686